Aeration and salt effects on indol acetic production by diazotrophic bacteria - Radwan, Tharwat El-Sayed El-Desouk; Mohamed, Mohamed Kamel; Reis, Veronica Massena (Pesquisa Agropecuaria Brasileira, 2005)
The production of indolic compounds by Azospirillum brasilense Cd, A. lipoferum Br 17, Herbaspirillum seropedicae Z 67, H. rubrisubalbicans M4, and strain 34 isolated from rice, which does not fit into the described Herbaspirillum species, was measured under aeration ratio and salt concentrations. Aeration of the medium increased growth and production of indole compounds by these bacteria. Under static condition, the production was higher both in nitrogen-free medium for Azospirillum, and in amended N medium for the Herbaspirillum strains. Increasing salt concentration into the medium inhibited the production of indole compounds, although a small increase in production was observed, when CaCl2 concentration was raised above 1 g L-1. Deleterious effect of salinity was more pronounced in the presence of NaHCO3, followed by NaCl and Na2SO4. Azospirillum produced more indolic compounds in semi-solid cultures, and Herbaspirillum in liquid medium, but at lower levels.
Keywords: Azospirillum; Herbaspirillum; auxin; indole-3-acetic acid; indole compounds